1991
DOI: 10.1152/jappl.1991.70.4.1544
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of diaphragmatic lymphatic stomata

Abstract: In seven anesthetized rabbits we measured the size, shape, and density of lymphatic stomata on the peritoneal and pleural sides of the diaphragm. The diaphragm was fixed in situ and processed for scanning electron microscopy. Results are from 2,902 peritoneal and 3,086 pleural fields (each 1,620 microns 2) randomly chosen from the various specimens. Stomata were seen in 9% of the fields examined, and in 30% of the cases they appeared grouped in clusters with 2-14 stomata/field. Stoma density was 250 +/- 242 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 0 publications
1
50
0
2
Order By: Relevance
“…Subsequent experiments confirmed that there were indeed physical channels existing in the mediastinal pleura of rats, implying that the anatomy of rat mediastinal pleura is different from that of human beings. Although stomas on the costal pleura and the diaphragm have been identified and confirmed previously [15,16] , there was previously no report on stomas on the mediastinal pleura, which is a thin membrane. Through light microscopy, we could observe stomas on the mediastinal pleura, as shown in Figure 7C-7D.…”
Section: Wwwchinapharcom Qin Zh Et Almentioning
confidence: 65%
“…Subsequent experiments confirmed that there were indeed physical channels existing in the mediastinal pleura of rats, implying that the anatomy of rat mediastinal pleura is different from that of human beings. Although stomas on the costal pleura and the diaphragm have been identified and confirmed previously [15,16] , there was previously no report on stomas on the mediastinal pleura, which is a thin membrane. Through light microscopy, we could observe stomas on the mediastinal pleura, as shown in Figure 7C-7D.…”
Section: Wwwchinapharcom Qin Zh Et Almentioning
confidence: 65%
“…The lymphatics provide drainage of the interstitial spaces but also of the pleural cavity, as they open directly on the parietal pleura (lymphatic stomata). Stomata, in rabbits and sheep [8][9][10][11], are frequently grouped in clusters and connect to an extensive network of submesothelial lacunae [11,12]. They range in density from 100 stomata·cm -2 on the intercostal surface to 8,000·cm -2 on the diaphragm and their diameter averages 1 µm (range <1-~40 µm) in size.…”
Section: The Pleural Compartmentsmentioning
confidence: 99%
“…During PD, however, only a minor portion (20 to 30%) of the total fluid and solute reabsorption seems to occur by the lymphatics (4 -7). True lymphatic absorption from the PC occurs from the peritoneal tissues and also via the lymphatic lacunae in the diaphragm (22,23). The latter have the ability to remove small particles up to the size of 10 m, thus even erythrocytes.…”
Section: Discussionmentioning
confidence: 99%